Should children be running ultramarathons? - Scheer, V.; Hoffman, M. D. (Current Sports Medicine Reports, 2018)
Ultramarathon races have gained popularity with there having been an approximately four-fold increase in the number of adult finishes over the last decade (1). While representing a much smaller number, the participation in ultramarathons by children and adolescents also has increased during the past decade. Growing requests of race directors to allow race entry of underaged athletes may place them, and the medical directors they may consult, in a dilemma. While ultramarathon participation guidelines have been published relative to various medical conditions (2,3), no such guidelines have been developed on age restrictions.